510. First Environmental Investigation of Toxigenic Clostridium difficile Strains in Texas Hospitals. (26th November 2018) - Alam, M Jahangir; Begum, Khurshida; McPharson, Jacob; Miranda, Julie; Hossain, Feroz; Poblete, Kelley; Garey, Kevin W
Abstract: Background: Clostridium difficile is the most common cause of infectious diarrhea in hospitalized patients in the developed world and an emerging pathogen in developing countries due to increased use of broad-spectrum antibiotics worldwide. Spores of toxigenic C. difficile can survive and disseminate in any environs and act as sources for human colonization or infections. Although likely ubiquitous in any environs, the prevalence of C. difficile spores in the hospital environment of Texas hospitals is poorly understood. The objectives of the study are to isolate and characterize C. difficile from the hospital environs of three hospitals in three cities in Texas. Methods: As part of a Texas hospital-wide surveillance effort, we collected shoe-bottom swabs samples from hospital employees, patients, and visitors inside three large hospital from three cities. Samples were analyzed for C. difficile using anaerobic enrichment culture and molecular methods. Suspected colonies from cycloserine cefoxitin fructose agar (CCFA) plates were identified by PCR ( tcdA, tcdB, cdtA, cdtB, tpi ) and genotyped using fluorescent PCR ribotyping. Results: A total 229 of 1079 (21.2%) surface swab and 81 of 121 (66.9%) shoe swab samples were culture positive for toxigenic C. difficile ( tcdA and tcdB ). A total of 29 distinct ribotypes were identified from 166 C. difficile isolates tested. Predominant ribotypes were F106, F019, F014-020, F002, and F255. Interestingly, ribotype F027 was not a predominant strain among the swab samples. Each hospital had widely diverse strains. Shoes were the most contaminated item in all the hospitals. Conclusion: We identified a high prevalence of toxigenic C. difficile with diverse ribotypes from hospital environmental shoe-bottom swabs and high touch surface swabs in hospitals in three cities of Texas. Our findings suggest that patients might be at higher risk for C. difficile colonization or infection in these hospitals. Disclosures: K. W. Garey, Merck & Co.: Grant Investigator, Grant recipient.